Separate Node Ascending Derivatives Expansion (SNADE) for Univariate Functions: Node Optimization via Partial Fluctuation Suppression - GÜRVİT, ERCAN (AMER INST PHYSICS, 2015)
This work's content finds its root in the material given in the first three companion papers on the very newly proposed method called Separate Node Ascending Derivatives Expansion (SNADE) for Univariate Functions. Those three and the present companion papers are to appear in this proceedings. This work focuses on the determination of the nodal values which make the Euclidean distance between the target function and the SNADE truncation polynomial under consideration. The minimization procedure uses certain elements of the mathematical fluctuation theory. We obtain nonlinear equations after the minimization of the Euclidean distance mentioned above. The solutions of these equations can be numerically obtained unless the target function has a very specific structure. This is a so-called baby age theory and needs very specific care for robustness and sophistication. Here, the purpose is just formalism and conceptuality. Practicality has been left to future works.
Keywords: Multinode Taylor expansion; Infinite interpolation; Integral representation; Bounds to integrals; Series convergence